2018
DOI: 10.1155/2018/4973851
|View full text |Cite
|
Sign up to set email alerts
|

Polysiphonia japonica Extract Attenuates Palmitate‐Induced Toxicity and Enhances Insulin Secretion in Pancreatic Beta‐Cells

Abstract: Beta-cell loss is a major cause of the pathogenesis of diabetes. Elevated levels of free fatty acids may contribute to the loss of β-cells. Using a transgenic zebrafish, we screened ~50 seaweed crude extracts to identify materials that protect β-cells from free fatty acid damage. We found that an extract of the red seaweed Polysiphonia japonica (PJE) had a β-cell protective effect. We examined the protective effect of PJE on palmitate-induced damage in β-cells. PJE was found to preserve cell viability and gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…It has been demonstrated that chronic hyperglycemia and higher levels of circulating FFAs are commonly associated with the beta cell function deterioration [2]. Hyperglycemia could aggravate lipotoxicity-induced beta cell dysfunction (glucolipotoxicity) [5, 6]. Recently, transcriptomics and proteomics have been successfully adopted to discover major changes of protein-coding genes and proteins in pancreatic INS-1 cells exposed to glucolipotoxicity [18, 19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that chronic hyperglycemia and higher levels of circulating FFAs are commonly associated with the beta cell function deterioration [2]. Hyperglycemia could aggravate lipotoxicity-induced beta cell dysfunction (glucolipotoxicity) [5, 6]. Recently, transcriptomics and proteomics have been successfully adopted to discover major changes of protein-coding genes and proteins in pancreatic INS-1 cells exposed to glucolipotoxicity [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic elevation of hyperglycemia causes beta cell failure characterized by impaired insulin secretion and enhanced islet beta cell apoptosis (glucotoxicity) [3, 4]. Furthermore, long-term exposure of beta cells to FFA triggers apoptosis (lipotoxicity) and the elevated glucose augments fatty acid-induced beta cell death (glucolipotoxicity) [57]. The glucolipotoxicity plays a pivotal role in the worsening of beta cell function over time, which has been implicated in the development of T2DM [8].…”
Section: Introductionmentioning
confidence: 99%
“…Dieckol also reduced overexpression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) [ 182 ]. A recent study addressed the efficacy of an extract of the red seaweed Polysiphinia japonica on preserving cell viability and glucose-induced insulin secretion in a pancreatic β-cell line, Ins-1, treated with palmitate [ 183 ]. However, the tested extract contained, in addition to polyphenols, other components such as carbohydrates, lipid and proteins; hence, the described bioactivities may not be due only to polyphenols.…”
Section: Bioactive Properties Of Marine Phenolicsmentioning
confidence: 99%
“…Evidence has suggested that continuous exposure to high concentrations of free fatty acids (FFAs) and glucose may damage islet β-cells, activate apoptosis, and in turn, generate glucotoxicity and lipotoxicity (31)(32)(33)(34). To test whether TG could have a protective role against glucotoxicity and lipotoxicity by increasing the expression of PDX1, we established a glucotoxicity (35,36) and lipotoxicity (32,37) models in islet β-cell lines. We observed that 200 μM palmitic acid (PA) or 33mM glucose (Glu) significantly decreased cell viability of INS-1 cells, which indicated that both lipotoxic and glucotoxic models were successfully established ( Fig.…”
Section: Tg Protects Ins-1 Cells From Apoptosis Induced By High-fat Amentioning
confidence: 99%